Safety and efficacy of intravesical chemotherapy and hyperthermia in the bladder: results of a porcine study. (1st January 2020) - Tan, Wei Phin; Chang, Andrew; Brousell, Steven C.; Grimberg, Dominic C.; Fantony, Joseph J.; Longo, Thomas A.; Etienne, Wiguins; Spasojevic, Ivan; Maccarini, Paolo; Inman, Brant A.
Abstract: Background: Hyperthermia (heating to 43 °C) activates the innate immune system and improves bladder cancer chemosensitivity. Objective: To evaluate the tissue penetration and safety of convective hyperthermia combined with intravesical mitomycin C (MMC) pharmacokinetics in live porcine bladder models using the Combat bladder recirculation system (BRS). Methods: Forty 60 kg-female swine were anesthetized and catheterized with a 3-way, 16 F catheter. The Combat device was used to heat the bladders to a target temperature of 43 °C with recirculating intravesical MMC at doses of 40, 80, and 120 mg. Dwell-heat time varied from 30–180 min. Rapid necropsy with immediate flash freezing of tissues, blood and urine occurred. MMC concentrations were measured by liquid chromatography tandem-mass spectrometry. Results: The Combat BRS system was able to achieve target range temperature (42–44 °C) in 12 mins, and this temperature was maintained as long as the device was running. Two factors increased tissue penetration of MMC in the bladder: drug concentration, and the presence of heat. In the hyperthermia arm, MMC penetration saturated at 80 mg, suggesting that with heating, drug absorption may saturate and not require higher doses to achieve the maximal biological effect. Convective hyperthermia did not increase the MMC concentration in the liver, heart, kidney, spleen, lung, and lymph node tissue even at the 120 mg dose. Conclusions: Convective bladder hyperthermia using the Combat BRS device is safe and the temperature can be maintained at 43 °C. Hyperthermia therapy may increase MMC penetration into the bladder wall but does not result in an increase of MMC levels in other organs.